The Effects of the Attention, Relevance, Confidence, and Satisfaction (ARCS) Model on Students’ Motivation in EFL Classroom. Case Study: 1st Year Middle School in Messaad- Djelfa - Eloued , Fatima Zahra; Beroman ,Meriem; Cherfaoui, Samia (Faculty of Letters and Foreign Languages Department of English, 2017)
English is seen as one of the most difficult modules for middle school students, so they tend to not put much of their attention to it. Teaching English using the attention, relevance, confidence, satisfaction (ARCS) motivational model created by John Keller, is expected to reduce the students’ difficulties in learning and it can help them increase their motivation to learn. The present study was designed to study the effects of the ARCS model on first year middle school class students’ motivation. For this purpose, experimental research was carried out in which ARCS motivational model strategies were inserted in a detailed lesson plans that were applied throughout four weeks. To find out the effects of ARSC model a modified version that combined both Course Interest Survey (CIS) and Instructional Materials Motivation Survey (IMMS) in one questionnaire was administered at the beginning and end of the study. The results of CIS showed a considerable increase where the overall CIS results at the end of the study showed that students have higher motivation concerning the course. CIS was evaluated in terms of each ARCS category and a considerable positive change was observed in all scales. As for IMMS results a substantial difference in students’ instructional motivation scores was found. The final results of the study showed that the ARCS model had positive influence on both students’ course and instructions motivation in all categories